2018
DOI: 10.26442/terarkh201890641-47
|View full text |Cite
|
Sign up to set email alerts
|

Serum uromodulin as an early biomarker of tubular atrophy and interstitial fibrosis in patients with glomerulopathies

Abstract: Aim. To assess the significance of the serum uromodulin (Tamm-Horsfall protein - THP) concentration (Sumo) as an early biomarker of tubular atrophy (TA) and interstitial renal fibrosis (IF) in patients with glomerulopathies. Materials and methods. 84 patients with glomerulopathy and 11 practically healthy persons (control) were examined. Uromodulin concentrations in serum and urine (Uumo) were measured, renal excretion of this protein and the estimated glomerular filtration rate (eGFR) were established. A semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
(36 reference statements)
0
6
0
1
Order By: Relevance
“…In the same manner, serum uromodulin has been linked to tubular atrophy in glomerulopathies that are not associated with SLE. Smirnov et al observed earlier changes in serum uromodulin levels in patients with a recent onset of tubular atrophy [ 31 ]. Serum uromodulin is an early biomarker for tubular atrophy and interstitial fibrosis in patients with glomerulopathies [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same manner, serum uromodulin has been linked to tubular atrophy in glomerulopathies that are not associated with SLE. Smirnov et al observed earlier changes in serum uromodulin levels in patients with a recent onset of tubular atrophy [ 31 ]. Serum uromodulin is an early biomarker for tubular atrophy and interstitial fibrosis in patients with glomerulopathies [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smirnov et al observed earlier changes in serum uromodulin levels in patients with a recent onset of tubular atrophy [ 31 ]. Serum uromodulin is an early biomarker for tubular atrophy and interstitial fibrosis in patients with glomerulopathies [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This correlation was further assessed using a simulated H/R model in vitro. Previous studies have reported that UMOD expression is closely associated with kidney diseases (3)(4)(5)(6)(7)(8)(9). It has been demonstrated that UMOD gene mutations result in familial juvenile hyperuricemic nephropathy, medullary cystic kidney disease type 2 and glomerulocystic kidney disease (8).…”
Section: Discussionmentioning
confidence: 99%
“…Uromodulin (UMOD) is the most abundant protein in normal human urine and is selectively expressed by epithelial cells of the thick ascending limb of Henle's loop and the early distal renal tubule (3,4). Previous studies have revealed that UMOD serves an important role in patients with acute and chronic kidney diseases (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Уромодулин (белок Тамма-Хорсфалла) -специфический почечный протеин, синтезирующийся исключительно в эпителиальных клетках толстого восходящего отдела петли Генле и начального отдела дистального извитого канальца. В последние годы возрос интерес к изучению концентрации уромодулина в сыворотке крови: показано, что концентрация уромодулина в сыворотке прямо ассоциировалась со СКФ, средним АД и обратно -с выраженностью атрофии канальцев, сывороточной концентрацией креатинина [11]. Более того, оказалось, что величина сывороточного уромодулина может являться более ранним и чувствительным маркером хронической почечной дисфункции, чем некоторые другие общепризнанные показатели (например, цистатин С) [12,13].…”
Section: îáñóAeäåíèå ðåçóëüòàòîâunclassified